Kepastian Hukum dalam Tanah adat dan UUPA yang mengatur Mengenai Tanah Adat - Margaret Pangaribuan; Donita Simanungkalit; Enjelina Sinaga; Nelly Hutapea; Putra Harahap; Grace Mikael; Ramsul Nababan (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to find out how legal certainty is in customary land and the UUPA which regulates customary land. The importance of legal certainty is also closely related to the concept of sustainable development. By providing legal clarity regarding customary land, the government can create a conducive environment for sustainable investment, while still paying attention to the welfare and rights of indigenous communities. This legal certainty also involves a fair and transparent resolution mechanism, so that land-related conflicts can be resolved without harming either party. Customary land is land that is regulated and managed based on the customary law of a customary law community. Customary land is usually owned and used communally by members of the indigenous community. The strong ties between traditional lands and traditional communities have been formed for hundreds of years and have been passed down from generation to generation. Traditional land has multifunctions, not just land for farming, but also being an integral part of the culture and identity of indigenous peoples. Land for them has very important social, economic, political and even religious values. Therefore, the relationship between indigenous peoples and land is magical-religious and institutionalized in everyday life. In Indonesia, customary land is still quite extensive, although it is not yet known exactly how much. The research methodology used in this research is descriptive qualitative. Three stages of research were carried out: (1) observation; (2) interview; and (3) documentation. The results of this research show how legal certainty is regarding traditional land in the Toba area through the sources interviewed